2014
DOI: 10.1177/1932202x14549250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Differentiated Reading Instruction on Student Achievement in Middle School

Abstract: Reading instruction often does not focus on appealing to student interests, offering choice, or responding to the needs of advanced readers. In this experimental study, we examined the effects on achievement of an instructional approach involving choice, differentiated instruction, and extensive, supported, independent reading, with corresponding elimination of regular reading instruction. The study, which incorporated multi-site cluster-randomized design, was conducted in four middle schools with 2,150 studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
11

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 18 publications
3
43
0
11
Order By: Relevance
“…These results are aligned with the previous research that revealed the positive impact of DI on students from elementary to college levels of education (e.g. Martin & Pickett, 2013;Konstantinou-Katzi, et al, 2013;Little, McCoach, & Reis, 2014), and also indicated the applicability and the positive impact of DI in kindergarten (Wu & Chang, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are aligned with the previous research that revealed the positive impact of DI on students from elementary to college levels of education (e.g. Martin & Pickett, 2013;Konstantinou-Katzi, et al, 2013;Little, McCoach, & Reis, 2014), and also indicated the applicability and the positive impact of DI in kindergarten (Wu & Chang, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, Koeze (2007) showed that DI facilitated the achievement of children from low socio-economic status, but DI's effectiveness was not repeated in the sum of students. Moreover, Little, McCoach, & Reis (2014) studied the reading performance of middle school students and found that DI was effective in reading fluency, but not in comprehension. Such conflicting findings imply that DI might be effective for specific groups of children and under certain circumstances.…”
Section: Effectiveness Of DImentioning
confidence: 99%
“…Since the main aim of DI is to increase the academic success of children, its impact on achievement has been the object of investigation for several researchers. Recent studies suggest that differentiated approach affected positively children's performance and enhanced motivation for learning (Koeze, 2007;Lewis & Batts 2005;Little, McCoach, & Reis, 2014;Tobin & Mc Innes, 2008;Tomlinson & McTighe, 2004). Most empirical studies focused on the effectiveness in reading (Little, McCoach, & Reis, 2014) and mathematics (Scott 2012;Tieso, 2005), while few evaluated differentiation in other fields, such as science education (Odgers, Symons, & Mitchell, 2000).…”
Section: Differentiated Instructionmentioning
confidence: 99%
“…Until the end of the program the participants acquired material and strategies to respond to the reading needs of their students. Little, McCoach, & Reis (2014) also organized a PDp with constant group meetings of teachers in order to familiarize them with the differentiated concept and provide additional support during the implementation. Similarly, Tobin & Tippett (2014) developed a PDp with 5 teachers, including group meetings where teachers engaged in a variety of presentations, short lectures, activities and discussions about DI.…”
Section: Professional Development Programs For Differentiated Instrucmentioning
confidence: 99%
“…Implementing differentiated instruction assists to engage disengaged readers. (Little, McCoach & Reis, 2014;Gambrell, 2011& Block&Pressley,2002 In order to effectively implement differentiated instruction in reading and engage students throughout the learning process, an effective teacher needs to know each child's skill level and have an idea of where the child should be (Tomlinson, 2006). Moreover, Latz, Neumeister, Adams and Pierce (2009) assured that in order to successfully implement differentiated instruction in classrooms; teachers must be willing to invest extra planning time and preparation not only to create more work for students, but also create different types of work.…”
Section: Introductionmentioning
confidence: 99%